Glicerina semipurificada neutralizada na alimentação de suínos - Gomez Gallego, Adriana (2012)
Three experiments were carried out in order to determine the nutritional value and evaluate the performance of pigs in the initial, growing and finishing phases. The pigs were fed with neutralized semi-purified glycerin (NSPG) in increasing levels. In Experiment I, a digestibility trial was carried with 30 crossbred pigs (24 for tests diets and6 for reference diet), with initial weight of 42, 91 1,58kg, allotted in experimental design of completely randomized blocks with five treatments (reference diet and test diets with 4, 8, 12 and 16% inclusion of NSPG) six replicates with experimental unit represented by an animal. The values of digestible energy (DE) and metabolizable energy (ME) of glycerin were estimated by regression analysis of DE and ME (kcal/kg) intake vs. glycerin intake (kg). The values obtained for the natural matterof ED and ME (kcal/kg) of NSPG were: 3.298 and 2.531, respectively. The results indicate that this type of glycerin is an energy source for swine feeding. In Experiment II, 100 piglets (15. 14 +- 0.06 a 30. 28+- 0. 65), were allotted in a randomized block design with four levels inclusion (3.5, 7.0, 10.5 and 14 %) of NSPG, with ten replicates and two piglets per experimental unit. Additionally, a control diet (CD) was formulated, without glycerin (0%). The performance results show that it is feasible to use up to 14% of NSPG, on piglets feeding without impairing performance and plasmatic variables, although it may provide an increase of about 2.9% in the diet cost. In Experiment III, 80 pigs were used in the growing (30.31± 0.47 a 60.41± 0.87 kg) and finishing (60.45±0.46 a 90.99±0.83 kg) phases, allotted in a randomized block design, with four levels of NSPG inclusion (3.5, 7.0, 10.5 and 14%), with sixteen replicates and one pig per experimental unit. Additionally, a control diet was formulated containing no glycerin (0%). At the end of the finishing phase all pigs were slaughtered to evaluate the quantitative traits of the carcass and qualitative traits of the meat. The regression analysis indicates that there was no effect (P>0.05) of NSPG inclusion on performance, backfat thickness and loin depth during the growing and finishing phase. For plasma variables, only in the finishing phase cholesterol and triglycerides increased linearly. However there was a linear increase for the quantitative variables of the carcass (P< 0.05) for hot carcass weight, hot carcass yield, cold carcass weight, and cold carcass yield, whereas for the qualitative variables, there was a quadratic effect for water drip loss and total lipids in the NSPG inclusion. The results from all experiments suggest that it is feasible to use up to 14% of NSPG in pigs feeding (15-90 kg), without impairing performance, plasmatic parameters and meat quality. However it led to an increase in the pig feeding cost of 2.9% in piglets (15-30 kg), of 8.5% in pigs of 30 to 60 kg and 3.8% in pigs of 60 to 90 kg, according to price relation of ingredients.